A residência multiprofissional para o SUS e para além do SUS : uma análise da inserção profissional de assistentes sociais egressas dos programas de residência de Porto Alegre - Oliveira Netto, Isadora Brinckmann (2024)
The overarching goal of this dissertation is to analyze, based on participants' perspectives, how the Multiprofessional Health Residency programs in Porto Alegre contribute to the integration of graduate social workers into socio-occupational spaces within the Brazilian Unified Health System (SUS), aiming to enhance the qualification of this process. The specific objectives are: 1) To ascertain whether the Integrated Multiprofessional Health Residency programs in Porto Alegre are contributing to the formation of human resources for SUS in compliance with current legislation; 2) To analyze the social experiences of participants regarding their integration into socio-occupational spaces after completing the Integrated Multiprofessional Health Residency; 3) To identify the methods of integrating these graduates into socio-occupational spaces and the types of competitions/selections through which this has occurred. The development of this research is grounded in the Historical Dialectical Materialism Method, which spans all stages of the study through the analysis of central analytical categories: totality, historicity, contradiction, and mediation. Given these objectives and the chosen methodology, a Qualitative research approach has been adopted, along with the Data Triangulation Technique, involving participant interviews, documentary analysis of Announcements and Selection Processes (2021, 2022 and 2023), as well as a literature review encompassing themes relevant to the research objectives. The intentional sample will comprise 14 participants, selected through convenience sampling using a snowball approach. In terms of the documents to be analyzed, an overview of the latest Contests and Selection Processes from all institutions offering positions for social workers in their Residency Programs was conducted. The collected information will be analyzed using Bardin's Content Analysis (1977). The study revealed an extremely contradictory reality regarding the completion of residency. It is observed that the offered scholarship is an important differential, especially concerning integration into the job market after graduation. Additionally, the research points to several difficulties that permeate residency, such as excessive workload, lack of preceptorship, and a poor understanding of the role of residents within institutions. Despite this, residency proves to be an important professional learning experience and personal growth opportunity. Furthermore, it is noted that there is no program or policy guaranteeing that professionals who graduate from residencies return to the public healthcare system (SUS). However, it is perceived that, according to the collected data, professionals are managing to return to the public service sector in general, especially to social assistance and health policies. Moreover, it is evident that completing residency impacts each participant differently, producing specific experiences and distinct perceptions regarding the profession and public service. The repercussion of completing residency on the professional performance of the participants is also identified, signaling inservice training as a potential for learning and improvement